Castro et al. Synthesis, Characterization, and Optimization Studies of Polycaprolactone/Polylactic Acid/Titanium Dioxide Nanoparticle/Orange Essential Oil Membranes for Biomedical Applications. Polymers (2023, 15, 135) - Zapata-Ramirez, P (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Sin Resumen Disponible